Iron as Preoperative Antituberculosis Supplement Increases Interleukin-12 Level in Spinal Tuberculosis and Iron Deficiency Patients (Jurnal Anestesi Perioperatif, 2020)
Iron deficiency remains the most prevalent micronutrient deficiency worldwide. Iron deficiency in TB patients, causes a poor outcome, reccurency, and treatment failure. Iron supplements on TB patients with iron deficiency will activate macrophage-derived monocytes (MDM) and interferon-gamma (IFN-Î³), with a positive feedback mechanism pushing interleukin-12 (IL-12). This study is a single-blind randomized control trial comparing the effectivity of preoperative iron supplementation in IL-12 level between two different groups in Dr. Hasan Sadikin General Hospital Bandung, conducted from November 2018 until March 2019. Respondents are those having Spondylitis TB, with sTfR > 21,7 pg/mL and IL-12
Keywords: Interleukin-12; iron supplementation; spinal tuberculosis